PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT FAST FOOD INDONESIA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011-2017 - Juwita Puspita Br Tarigan (Universitas Medan Area, 2020)
This study aims to determine the effect of Current Ratio and Debt to equity ratio on stock prices at PT. Fast Food Indonesia Tbk. The type of research conducted is Causal Associative research which aims to analyze the relationship between one variable with another variable or how a variable affects other variables. The population in this study is the financial statements of PT. Fast Food Indonesia Tbk period 2011-2017. Based on the results of the CR t test has a significance of 0.297 0.05 and has a regression coefficient of 6.914 which means that CR has a positive effect on the stock price of PT. Fast Food Indonesia Tbk. DER has a significance value of 0.023 0.05 and has a regression coefficient of -30.009 which means that DER has a negative and significant effect on stock prices. Based on the results of the F, CR and DER test has a significance value of 0.035 0.05 and shows the value of Fcount Ftable 8.765 6.944 which means that simultaneously CR and DER have a positive and significant effect on the Stock Price. The value of the coefficient of determination (R2) is 0.902. So it can be concluded that the dependent variable (stock price) is influenced by the independent variable (Current Ratio, Debt to equity ratio) of 81,4%. And the remaining 18,6% is influenced by other variables not examined in this study